THE REASONS FOR GENERAL JO‘RABEK’S TRANSITION TO THE SERVICE OF THE TURKESTAN GENERAL-GOVERNORATE: AN ANALYSIS OF HISTORICAL - Parmonov Sharafiddin Shavkatovich (Western European Studies, 2025)
This article examines the reasons behind the transition of Jurabek and Babobek— who were active in the Shahrisabz Bekdom during the 1860s–1870s—into the service of the Russian Empire. It explores their capture by the Kokand Khan Khudoyarkhan and their subsequent acceptance into the service of General von Kaufman, based on contemporary historical sources
Keywords: Bukhara Emirate; Kokand Khanate; Russian Empire